Xinjiang in Central Asia's Regional Security Structure. (January 2015) - Debata, Mahesh Ranjan
The emergence of five Central Asian Republics (CARs) following Soviet collapse in 1991 created a new geopolitical situation, with the USA, Russia and the People's Republic of China (PRC) emerging as key players. China has become one of the strongest forces to take advantage of this new opportunity, be it trade, energy, or to safeguard its volatile Xinjiang region that shares border with three CARs: Kazakhstan, Kyrgyzstan and Tajikistan. Further, inimical forces such as terrorism, religious extremism, transnational drug trafficking, smuggling of arms and ecological disaster have dealt a body blow to regional peace and stability, thereby creating a shattered security zone in and around Central Asia. Given this backdrop, this article argues that security issues, which have so far been important, are going to pose serious challenge in the coming years. It describes Xinjiang as the main geopolitical anchor in Central Asia's security structure with all its potential for a possible conflagration in the region.